PENGARUH KEBIJAKAN DIVIDEN, KEPUTUSAN PENDANAAN, PERATAAN LABA DAN KEPEMILIKAN INSTITUSIONAL TERHADAP BIAYA KEAGENAN PADA PERUSAHAAN SEKTOR INDUSTRI PERTANIAN DAN SEKTOR INDUSTRI DASAR YANG TERDAFTAR DI BEI PERIODE 2011-2015 - Martha Ayerza (Jurnal Manajemen, 2017)
The purpose of this study is to examine the effect of dividend policy, funding decision, income smoothing, and institutional ownership of agency cost. The population in this study are all companies of agriculture industry sector and basic industry sector listed on Indonesia Stock Exchange from 2011 until 2015 period. The theory underlying this research is agency theory and cash flow theory. Regression analysis using data from the company's financial statements of sample amounted to 20 companies that have been processed. This research yields the following: 1. Variable dividend policy proved to have no effect on agency cost, 2. Variable of funding decision not proven to have influence to agency cost, 3. Income smoothing proved to have influence to agency cost, 4. Institutional ownership proven to have influence on agency costs in agricultural and industrial sector industries.Â Key word: Dividend Policy, Funding Decision, Income Smoothing, Institutional Ownership, Agency Costs